VARIASI GENETIK MONASCUS PURPUREUS YANG DIISOLASI DARI BERAS MERAH CINA - Suharna, Nandang (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTGenetic Variation of Monascus purpureus Isolated from Chinese Red Rice. An attempt was carried out to detect genetic variation among six Monascus purpureus isolates by RAPD finger printing. The isolates studied were isolated from Chinese red rice (ang-kak) collected from Indonesian markets. Seven types of oligonucleotide 12-mer primers were used in this study. These primers were different from G+C ratio (42%, 50%, 68% and 75%) so as to know the best ratio for DNA amplication. Products of DNA amplication by seven primers were observed such as 158 banding patterns, comprise of 23 common fragments and 135 polimorfic fragments. The result showed that the six isolates were divided into two groups based on DNA banding patterns. The same grouping was also shown by phylogenetic analysis. This analysis indicated two cluster which were different from its genetic distance (49%) and two pairs of isolates were identical to each other. So far, this RAPD analysis proved that there was high genetic variation within the six isolat of M. purpureus. It was assumed that there was a tendency of species separation within those isolates. It is suggested that sequencing analysis on 18S rDNA should be carried out to ensure status of M.purpureus species used in ang-kak production.Key words: Monascus purpureus, variation, genetic, Chinese red-rice, RAPD